How to retain Generation Y employees? - Fuchs, Rosa María (2021)
This study aims to understand the relationship that work-life balance and the perception of organizational support to work-life balance have with job embeddedness (construct that measures the reasons to remain in the organization) in the case of professionals belonging to Generation Y. A quantitative cross-sectional study was developed using instruments adapted from the literature. The sample consists of 211 members of generation Y with three or more years of work experience. The results of the analysis show that there is a positive relationship between work-life balance and job embeddedness in the sample of members of Generation Y. The study is relevant for both academic and professional aspects. The literature reviewed did not present a consensus on work-life balance and its relationship with job embeddedness; therefore the results help to understand this relationship. Likewise, this study focuses on work-life balance independently and not as the absence of conflict. In addition, in response to the demand from literature, young people from Generation Y have work experience in the sample. Considering work-life balance as a relevant factor generates the creation of organizational retention policies.